National and sub-national trends of salt intake in Iranians from 2000 to 2016: a systematic analysis - Ali Gholami; Ali Ghanbari; Shahabeddin Rezaei; Hamid Reza Baradaran; Shahab Khatibzadeh; Mahboubeh Parsaeian; Mitra Hariri; Negar Zamaninour; Ali Sheidaei; Morteza Abdollahi; Parvin Mirmiran; Majid Ghayour-Mobarhan; et al. (BMC, 2022)
Abstract Background One fifth of the global burden of cardiovascular diseases (CVDs) in 2017 was attributable to excessive salt intake. As a member of the World Health Organization (WHO), Iran has committed itself to a 30% reduction in salt intake by 2025. Evidence on the amount and trend of salt intake among the Iranian population at national and sub-national levels is scarce. This study aimed to estimate the Iranian population's salt intake during 2000-2016 at the national and sub-national levels, by sex and age groups. Methods Data on national and sub-national mean salt intake was obtained through systematically searching the literature and contacting the research studies' principal investigators. Data collected through various methods were harmonized using the cross-walk method. Bayesian hierarchical and spatio-temporal-age regression models and simulation analysis were used to estimate the mean salt intake and its uncertainty interval across sex, age, year, and province. Results National age-sex standardized mean salt intake decreased from 10·53 g/day (95% uncertainty interval [UI]: 10·2 to 10·9) in 2000 to 9·41 (9·2 to 10·6) in 2016 (percent change: − 9·8% [− 21·1-3·1]). The age-standardized mean salt intake in women had decreased from 9·8 g/day (95% UI: 9·0-10·6) in 2000 to 9·1 g/day (8·6-9·7) in 2016 (percent change: − 6·6% [− 19·0-7·9]). The same measure in men was 11·1 g/day in 2000 (95% UI: 10·3-11·8) and 9·7 g/day (9·1-10·2) in 2016 (percent change: − 12·7% [− 23·0 - -0·9]). Age-sex standardized mean salt intake at the sub-national level in 2016 varied from 8·0 (95% UI: 7·0-9·0) to 10·5 (10·0-11·1). The difference between the provinces with the highest and the lowest levels of salt intake in 2016 was 31·3%. Conclusion Salt intake decreased in Iran from 2000 to 2016, while persistently exceeding the recommended values. This declining trend was more pronounced between 2010 and 2016, which might be attributed to Iran's compliance to WHO's Action Plan for reducing NCDs.